Detection and isolation of circulating exosomes and microvesicles for cancer monitoring and diagnostics using micro-/nano-based devices. Issue 2 (17th September 2015) - Ko, Jina; Carpenter, Erica; Issadore, David
Abstract : We explore emerging micro and nano-technology that isolates and detects exosomes and microvesicles in clinical samples for cancer diagnostics. Abstract : In the last several years, nanoscale vesicles that originate from tumor cells and which can be found circulating in the blood ( i.e. exosomes and microvesicles) have been discovered to contain a wealth of proteomic and genetic information to monitor cancer progression, metastasis, and drug efficacy. However, the use of exosomes and microvesicles as biomarkers to improve patient care has been limited by their small size (30 nm–1 μm) and the extensive sample preparation required for their isolation and measurement. In this Critical Review, we explore the emerging use of micro and nano-technology to isolate and detect exosomes and microvesicles in clinical samples and the application of this technology to the monitoring and diagnosis of cancer.